2003
DOI: 10.1111/j.1755-6988.2003.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Common Misconceptions in Addressing Domestic Violence in Child Custody Disputes

Abstract: Domestic violence has been recognized as an important factor to consider in determining the best interests of children in custody and visitation disputes. However, there remain many misconceptions about the extent and impact of domestic violence in child custody proceedings. Several misconceptions are identified and juxtaposed with the reality of emerging knowledge in this field, and implications are outlined. These issues are illustrated by the perspectives of 62 women victims and 95 children exposed to domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 19 publications
12
46
0
8
Order By: Relevance
“…Many judges and evaluators find it easier to believe that many women in custody litigation are lying or disordered. 9 Although the consistent data indicate that the majority of litigated, contested custody cases (a tiny proportion of all divorcing families) do involve a history of some partner violence, (Jaffe, Crooks, & Poisson, 2003;Johnston, 1994;Johnston & Campbell, 1988), courts still harbor the mistaken belief that most abuse allegations in custody litigation are fabricated. 10 Moreover, some degree of at least implicit gender bias cannot be ruled out.…”
Section: Historical Perspective 241mentioning
confidence: 99%
“…Many judges and evaluators find it easier to believe that many women in custody litigation are lying or disordered. 9 Although the consistent data indicate that the majority of litigated, contested custody cases (a tiny proportion of all divorcing families) do involve a history of some partner violence, (Jaffe, Crooks, & Poisson, 2003;Johnston, 1994;Johnston & Campbell, 1988), courts still harbor the mistaken belief that most abuse allegations in custody litigation are fabricated. 10 Moreover, some degree of at least implicit gender bias cannot be ruled out.…”
Section: Historical Perspective 241mentioning
confidence: 99%
“…Cette question est très importante, car les situations typiquement catégorisées comme hautement conflictuelles cacheraient, dans les faits, une importante réalité de violence conjugale (Jaffe et al, 2003;Johnston, 1994). Par ailleurs, deux études (Kernic et al, 2005;Morrill et al, 2005) basées sur de larges échantillons de dossiers de garde montrent que le système de justice peine à détecter la violence conjugale et à mettre en place des mesures adéquates pour protéger les victimes dans les ordonnances concernant la garde et les droits d'accès.…”
Section: Les Séparations Hautement Conflictuellesunclassified
“…Cette question est d'une grande importance, puisqu'elle a un impact durable sur le vécu d'enfants et de familles particulièrement vulnérables. À cet effet, il faut considérer que parmi les enfants qui vivent la séparation de leurs parents, ceux dont la garde et les droits d'accès sont disputés deviennent un enjeu important du conflit entre ex-conjoints : ils sont à risque d'être pris à partie (triangulés) dans les querelles entre leurs parents (Drapeau et al, 2004;Johnston et al, 2009) et même d'être exposés à la violence conjugale (Ayoub et al, 1999;Jaffe et al, 2003;Johnston et Campbell, 1993b). Bien que l'ordonnance de la cour ou l'expertise psychosociale ne représentent que des moments ponctuels dans un processus de séparation qui peut s'étaler sur des années, ces expériences peuvent être déterminantes et être aussi bien traumatisantes que thérapeutiques.…”
Section: Introductionunclassified
“…Perpetrators may use litigation as a form of ongoing control and harassment. The family court litigation process can become a tool for abusers to continue their control and emotionally abusive behavior in a new forum (Jaffe, Crooks & Poisson, 2003). Some authors have suggested that some abusive spouses have the skills to present themselves positively in court and convince evaluators and judges to award them custody (Bowermaster & Johnson, 1998;Zorza, 1995).…”
Section: Relevance Of Domestic Violence In Child Custody and Visitatimentioning
confidence: 99%
“…(Hotton, 2001;Liss & Stahly, 1993). Promoting contact between children and a violent ex-spouse may create an opportunity for renewed abuse of a former spouse through visitation and exchanges of children (Jaffe, Crooks, & Poisson, 2003;Sheeran & Hampton, 1999). .…”
Section: Relevance Of Domestic Violence In Child Custody and Visitatimentioning
confidence: 99%